Retracted: Ras‐PI3K‐AKT signaling promotes the occurrence and development of uveal melanoma by downregulating H3K56ac expression. Issue 9 (15th February 2019) - Li, Yaping; Sun, Dajun; Sun, Weixuan; Yin, Dexin
Abstract: Background: Uveal melanoma (UM) is an intraocular malignant tumor characterized by rapid progression and recurrence. The current conventional treatments are unsatisfactory. Histone acetylation at H3 lysine 56 (H3K56ac) has been reported to be a tumor suppressor in breast cancer. However, whether H3K56ac prevents the occurrence and development of UM remains uninvestigated. The study aimed to explore the regulatory effect of H3K56ac on Ras‐PI3K‐AKT induced UM cells proliferation and migration. Methods: The vectors of pEGFP‐Ras WT, pEGFP‐K‐Ras G12V/Y40C, and pEGFP‐N1 were transfected into MP46 cells, and protein levels of phosphorylated AKT Ser473 and H3K56ac were examined using western blot analysis. The effect of H3K56ac on cell proliferation and migration were studied using 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5 diphenyl tetrazolium bromide, colony formation, and Transwell assays. Reverse transcription‐quantitative polymerase chain reaction (RT‐qPCR) and chromatin immunoprecipitation assays were performed to determine the phosphoinositide 3‐kinase/protein kinase B (PI3K/AKT) downstream genes. Further, the regulatory effects of silent mating type information regulation 2 homolog‐1 (SIRT1), general control nonderepressible 5 (GCN5), and mouse double minute 2 homolog (MDM2) on Ras‐PI3K‐AKT affected H3K56ac expression were also investigated. Results: H3K56ac expression was specifically downregulated by Ras‐PI3K‐AKT activation pathway. H3K56ac inhibited the tumorigenic effect of Ras‐PI3K‐AKT on MP46 cells viability, colony formation, and migration, as well as participated in regulating the transcription of PI3K/AKT downstream genes. SIRT1 silence recovered H3K56ac expression, and reversed the tumorigenic effect of Ras‐PI3K‐AKT activation on MP46 cells. Downregulation of H3K56ac induced by Ras‐PI3K‐AKT activation was found to be associated with MDM2‐mediated the degradation of GCN5. Conclusions: The results demonstrated that Ras‐PI3K‐AKT signaling promoted UM cells proliferation and migration via downregulation of H3K56ac expression, which might be related to MDM2‐mediated the degradation of GCN5. Abstract : The results demonstrated that Ras‐PI3K‐AKT signaling promoted UM cells proliferation and migration via downregulation of histone acetylation at H3 lysine 56 (H3K56ac) expression, which might be related to MDM2‐mediated the degradation of GCN5.